High-temperature thin-film thermocouple for aero-engines - Keying Guo; Yazhong Lu; Zhihui Liu (PLoS ONE, 2025)
A thin-film thermocouple sensor directly deposited on nickel-based superalloys was investigated for aero-engine applications. To address the high-temperature and harsh environment challenges, the sensor’s film structure was meticulously designed. A NiCrAlY thin-film transition layer was deposited via magnetron sputtering, while an Al₂O₃ thin-film insulation layer and protective layer were prepared using electron beam evaporation and RF magnetron sputtering. Additionally, a Pt10Rh/Pt thin-film sensitive layer was fabricated via DC magnetron sputtering. Results indicate that the thin-film thermocouple sensor can operate at temperatures up to 1100 °C, with a Seebeck coefficient of 8.16 μV/°C, a maximum temperature error below ±1%, and a service life exceeding 20 hours. This sensor withstands the harsh conditions of aero engines, significantly improves local temperature measurement accuracy, and offers valuable insights for turbine blade lifespan and cooling design.